Market requirements and the accounting graduates / Abdul Samad Haji Alias (Universiti Teknologi MARA, Terengganu, 1991)
This article examines the changing roles and functions of accountants as dictated by the market situation in the complex business world of today and based on present day market requirements and the expectations of the profession as a whole, evaluates the average accounting graduate. Some shortcomings are identified for the attention of the institutions that produce them, along with suggestions that it is hoped are worthy of consideration.